Paraconsistent Doxastic Logic - Tworak, Zbigniew (Sensus Historiae, 2022)
Both in everyday-life situation and in science, we often deal with inconsistent information. From one reliable source we learn a certain piece of information, while from another one we get some information that contradicts this. In classical logic representing inconsistent information cannot be done non-trivially. In this paper, I develop a three-valued paraconsistent doxastic logic, which is intended to model inconsistent information states. I present „static” and „dynamic” versions of the logic. The systems reflects the idea that having inconsistent beliefs does not imply believing everything.